2016
DOI: 10.21831/jpai.v13i2.10304
|View full text |Cite
|
Sign up to set email alerts
|

Motivasi Belajar Pada Mahasiswa

Abstract: Penelitian ini bertujuan untuk mengetahui dan menganalisis mengenai motivasi belajar mahasiswa, dengan menggunakan alat ukur yang diadopsi dari MSLQ. MSLQ merupakan kuesioner yang digunakan untuk mengukur motivasi belajar mahasiswa, mengetahui pengaruh motivasi belajar terhadap prestasi akademik mahasiswa, serta melihat perbedaan motivasi belajar mahasiswa berdasarkan program studi dan gender. Responden penelitian ini adalah mahasiswa STIE Musi yang aktif dari program studi manajemen dan program studi akutansi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
17

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 2 publications
1
13
0
17
Order By: Relevance
“…There is no significant difference between male student learning motivation and female student learning motivation because both male and female visually impaired students can receive the same way of teaching from the same teacher. The result follows the research conducted by Mendari and Kewal (2015), which concluded that there was no difference in learning motivation by gender. Tabel 5 The results of differences in learning motivation scores based on school level Based on the results of the Table 5, Sig.…”
Section: A Differences In Learning Motivation Scores By Gendersupporting
confidence: 85%
“…There is no significant difference between male student learning motivation and female student learning motivation because both male and female visually impaired students can receive the same way of teaching from the same teacher. The result follows the research conducted by Mendari and Kewal (2015), which concluded that there was no difference in learning motivation by gender. Tabel 5 The results of differences in learning motivation scores based on school level Based on the results of the Table 5, Sig.…”
Section: A Differences In Learning Motivation Scores By Gendersupporting
confidence: 85%
“…According to Mendari, A. S., & Kewal, S. S. (2015) In learning motivation, there were 3 components, namely: (a) control belief component (b) Self-efficacy component refers to the intrinsic value components the drive to do something requires an intrinsic drive, which comes from within the individual. This encouragement was in the form of feeling happy with the lecture material, pleasant classroom atmosphere, and challenging assignments given by the lecturer so that they could improve their abilities; (c) Anxiety component is the anxiety level of an individual.…”
Section: B Review Of Literature Motivationmentioning
confidence: 99%
“…Manusia memerlukan dorongan, arahan, gerakkan agar dapat dikendalikan untuk mencapai tujuan yang diinginkan (Anas, 2014). (Mendari & Kewal, 2016) menyeburkan bahwa dunia pendidikan maupun dunia kerja tentu membutuhkan pengetahuan tentang manajemen agar suatu kegiatan memiliki target dan tujuan dengan menggunakan perencanaan, pengarahan serta pengorganisasian dalam mencapai tujuan tersebut. Menjadi penting hukumnya untuk setiap mahasiswa agar bisa mengelola manajemen waktu (time management), karena manusia bukanlah mesin yang dapat melakukan pekerjaan secara bersamaan (multi tasking).…”
Section: Pendahuluanunclassified